The Effect of Health Education on the Behavior of Elderly with Hypertension - Asni Hasanuddin; Muh Khidri Alwi; Ricvan Dana Nindrea; Astuti Astuti; Nilam Fitriani Dai; Andi Maryam; Ardiansah Hasin; La Ode Asrianto (Jurnal Penelitian Pendidikan IPA, 2023)
Education is one way that can be used to increase one's knowledge. Education can be given in various fields, including health. The purpose of this study was to determine the effect of Health Education on increasing the knowledge, attitudes and behavior of elderly people with hypertension in the Pangkajene Health Center area in 2023. This type of research used a quantitative method with a pre-experimental design study with pre-test and post-test design treatment, while the population was patients 90 people who suffer from hypertension at the Pangkajene Health Center use total sampling. The results of this study used the Wilcoxon test analysis. Knowledge was -8.132 and a significant value was 0.000 (p<0.05), Attitude was -8165 and a significant value was 0.000 (p<0.05), and Behavior was -8267 and a significant value was 0.000 ( p<0.05), there was a significant difference in the results of the Health Education pretest and posttest on the attitudes of the elderly with hypertension in the Pangkajene Health Center area. The results of this study indicate that there is an effect of Health Education on the attitude of the elderly who experience hypertension in the Pangkajene Health Center area. The conclusion of the study showed that there was an effect of Health Education on the knowledge, attitudes and behavior of elderly people with hypertension in the Pangkajene Health Center area. it is expected that the puskesmas will carry out home care because elderly people with hypertension cannot carry out health checks because there is no family to take them to health services because they are busy with their daily activities.